The boundaries of hate speech: law and reality - Kępa-Figura, Danuta (Papers in Linguistics, 2020)
The reasons for exploring hate speech in this article were: the significance of this category in the Polish public discourse in the second decade of the 21st century; lack of consensus as to what phenomenon it falls within the scope of this category; a need for a legal, statutory definition of this term. The main aims of the article were to capture the moment when the meaning of the notion of hate speech broadened, to discover factors determining this broadening, and to assess the validity of a postulate to make hate speech a legal term. To realize the research objectives a selection of texts representing anti-discrimination discourse was analysed as the greatest impact on the broadening of the meaning of hate speech is wielded by entities involved in the protection of minority rights (in particular the rights of sexual minorities). The characteristics of this non-legal understanding of hate speech are listed, taking into account a linguistic, a sociological and a psychological perspective. The article distinguishes the characteristics of hate speech that – according to the entities involved in the defence of minority rights – are decisive for the inclusion of homophobic discourse within the scope of hate speech. It also discusses those features that are decisive for the identification of cases of hate speech in the field of symbolic violence, caused by contempt or hatred. Taking into account the fact that broadening the non-legal understanding of hate speech does not have to imply penalizing all its manifestations, and allowing for diverse interferences between the legal and the non-legal understanding of hate speech, the postulate of turning this concept into a legal term was found unjustified. It was also shown that when there is a balance between being a minority and being a sufficiently large/visible minority, broadly understood hate speech is taken into account in the legislative reality.